2020
DOI: 10.1136/bmj.l6985
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants of gender inequality: why they matter for adolescent girls’ sexual and reproductive health

Abstract: More comprehensive understanding of gender inequality is required, particularly the broader structural drivers that underpin the political economy of gender power relations, say Asha George and colleagues

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 24 publications
1
66
0
1
Order By: Relevance
“…On the other hand, it is evidenced in the current study and other studies, that access to media increases HIV-related knowledge. Studies have shown that females are more economically disadvantaged and have less access to media than males in many countries [48,49]. Therefore, gender disparities in HIV-related knowledge between males and females may also be due to differences in accessing media.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is evidenced in the current study and other studies, that access to media increases HIV-related knowledge. Studies have shown that females are more economically disadvantaged and have less access to media than males in many countries [48,49]. Therefore, gender disparities in HIV-related knowledge between males and females may also be due to differences in accessing media.…”
Section: Discussionmentioning
confidence: 99%
“…From a societal lens, gender inequality as an intersectional and structural driver of adolescent health [23] must be further addressed for the GFF investments to be socially relevant, transformative and effective. It is the key social determinant underlying adolescent pregnancy, vulnerability to HIV and STIs, violence against adolescent girls and women, female genital mutilation and stigma related to menstruation [24] [25].…”
Section: Discussionmentioning
confidence: 99%
“…We discuss three cross-cutting issues in more detail: early discharge from hospital against medical advice; post-discharge treatment-seeking behavior and recovery; and concerns about inappropriate use of antibiotics. In a separate paper, we explore the gender issues and in uences in more depth, given that contextually relevant gender analyses are needed to improve health-related interventions, programs and policies [35,36].…”
Section: Discussionmentioning
confidence: 99%